An extended siderophore suite from Synechococcus sp. PCC 7002 revealed by LC-ICPMS-ESIMS1. Issue 5 (13th May 2015) - Boiteau, Rene M.; Repeta, Daniel J.
<x xml:space="preserve">Abstract</x> New members of the synechobactin siderophore suite with variable hydroxamate chain length were discovered using an LCMS based pipeline for the sensitive characterization of iron complexes.